EFFECT OF SKILLS AND WORK COMMITMENT ON EMPLOYEE PERFORMANCE AT PT. KAMPAR TUNGGAL AGRINDO KAMPAR DISTRICT - Muhammad Rizki Annur; Librina Tria Putri; Mustafa Kamal; Muhammad Yusril (STIE Bangkinang Publishing, 2022)
This reserch aims to determine the effect of skills and work commitment on the performance of PKS employees at PT. Kampar Tunggal Agrindo, Kampar Regency. The population in this study were all PKS employees at PT. Kampar Tunggal Agrindo by using the slovin technique by determining the sample to be 57 employees. Data collection techniques used are questionnaires and research files. The data analysis technique used is multiple linear regression analysis with a significant level (α) of 0.05. The results of this study conclude that skills and work commitment affect the performance of PKS PT. Kampar Tunggal Agrindo with a significant value less than 0.05. The results of the study using a partial test that work commitment has more influence on employee performance. There is a strong relationship between the variables of skills and work commitment to employee performance at PKS PT. Kampar Tunggal Agrindo.